SOME POSSIBILITIES AND DATA FOR OMPARINGTHE EARLY MODERN LVIV AND VILNUSHISTORICAL TOPOGRAPHY AND URBANONYMY (City: History, Culture, Society, 2026)
This article presents a comparative analysis of the spatial development and naming practices of two leading cities in East-Central Europe during the early modern period—Lviv and Vilnius. Both cities were founded in the 13th–14th centuries andshare a number of structural and historical features. Their origins are tied to princely legends; early settlements formed around castles on elevated terrain; and the development of urban centers occurred following the arrival of German settlers who introduced legal systems based on Magdeburg and Chełmno law. At the same time, the spatial planning and administrative organization of these cities diverged significantly, revealing broader patterns in the evolution of medieval and early modern cities in the region.The authors draw on archaeological findings, legal and fiscal sources, and historical maps to trace how these cities developed from a “castle–suburb” model into more complex structures that included jurydykas, suburbs, and urban villages. Special attention is given to naming practices—particularly of streets and city gates—as markers of memory, spatial organization, and legal authority. Referring to Ferdinand Opll’s typology of city gate names, the article reveals symbolic differences between the two urban landscapes: in Vilnius, gate names typically pointed to nearby settlements, while in Lviv, they referred to distant cities.The article also explores how various ethnic and religious communities—Germans, Jews, Armenians, Ruthenians, Tatars, and others—shaped both the structure of the city and its naming conventions. Through examples such as Jewish Street (platea Judeorum), Ruthenian Street (platea ruthenicali), and Dominican Street (ulica ku Dominicanom/Dominikonų gatvė), the authors show how toponyms reflected community presence.The spatial vocabulary of both cities is analyzed in the broader context of the “spatial turn” in urban history, particularly through the lens of Edward Soja’s ideas. In conclusion, the article shows that comparative urban studies help to understandbetter how city space was interpreted and organized. At the same time, it opens possibilities for interdisciplinary dialogue between researchers of Lviv and Vilnius.  Such dialogue can support mutual borrowing of approaches and methods: for example, in Lviv, studies on historical topography and urban names are more developed, while Lviv-based researchers could also learn from the archaeological practices used in Vilnius for studying the urban space.
Keywords: comparative studies, early modern period, urbanonim, Lviv, Vilnius